Окремі напрями законодавчого оновлення оцінювання медичних технологій за умов розвитку інноваційної діяльності - Михайліченко, Олександр (Видавництво ЛОБФ "Медицина і право", 2026)
Стаття досліджує сучасний стан нормативного регулювання оцінювання медичних технологій (ОМТ) в Україні за умов еволюції інноваційної діяльності у сфері охорони здоров’я (MedTech). Обґрунтовано необхідність розглядати державне ОМТ не лише як порядок добору технологій, а і як інструмент реалізації державної інноваційної політики. Увагу зосереджено на висвітленні систем штучного інтелекту як нового об’єкта та інструменту ОМТ (з урахуванням європейських підходів і міжнародної практики). Запропоновано зміни до Постанови Кабінету Міністрів України № 1300 з метою адаптації ОМТ до пріоритетів стратегічних документів і підготовки настанови ОМТ щодо штучного інтелекту на основі міжнародних практик.

The article examines the current state of legal regulation of health technology assessment (HTA) in Ukraine in the context of rapid innovation development of the national healthcare sector. It substantiates the need to perceive state HTA not merely as a procedural mechanism for selecting medical technologies, but as an institutional instrument for implementing public innovation policy. Particular attention is paid to medical technologies based on artificial intelligence, which are considered both an emerging area of HTA and a potential tool for improving assessment processes, in line with European Union regulations and international best practices. The study analyzes inconsistencies between strategic policy documents in the fields of healthcare and innovation and the existing regulatory framework for HTA, including the Cabinet of Ministers of Ukraine Resolution No. 1300. The current HTA procedure remains largely focused on medicinal products and does not fully address digital health solutions, artificial intelligence systems, or other advanced MedTech innovations prioritized by national strategies, though such situation is surely influenced by wartime conditions. The article proposes legislative amendments to align HTA regulation with strategic innovation priorities, including the explicit recognition of digital and AI-based medical technologies as independent objects of assessment. In addition, the feasibility of developing a dedicated HTA guideline for artificial intelligence systems is justified, drawing on the experience of the European Union, NICE (United Kingdom), Digi-HTA (Finland), and CADTH (Canada). The author concludes that, under appropriate regulatory conditions, HTA can serve as an effective mechanism for stimulating innovation while ensuring patient safety, economic efficiency, and a balance between public and private interests in the healthcare system.
Certain Directions of Legislative Modernization of Health Technology Assessment in the Context of Innovative Development
Certain Directions of Legislative Modernization of Health Technology Assessment in the Context of Innovative Development
Keywords: інноваційна діяльність у сфері охорони здоров’я; MedTech; медичні технології; медичні вироби; оцінювання медичних технологій; медичне право; економічне право; medical technology assessment; healthcare innovation; MedTech; medical technologies; medical devices